Critical behavior in fiber bundle model: A study on brittle to quasi-brittle transition. (12th November 2015) - Roy, Subhadeep; Ray, Purusattam
Abstract: We report a critical behavior in the breakdown of an equal-load-sharing fiber bundle model at a dispersion of the breaking threshold of the fibers. For, there is a finite probability P b, that rupturing of the weakest fiber leads to the failure of the entire system. For, . At, with, where L is the size of the system. As, the relaxation time τ diverges obeying the finite-size scaling law: with . At, the system fails, at the critical load, in avalanches (of rupturing fibers) of all sizes s following the distribution, with . We relate this critical behavior to the brittle to quasi-brittle transition in the model. For the local-load-sharing scheme, the system is found to be always brittle for sufficiently large system sizes.